Nucleotide and haplotypic diversity of the NOS2A promoter region and its relationship to cerebral malaria. - Burgner, D; Usen, S; Rockett, K; Jallow, M; Ackerman, H; Cervino, A; Pinder, M; Kwiatkowski, D (2003)
To assess the hypothesis that nitric oxide is critical in the pathogenesis of cerebral malaria, we analysed genetic variation in the proximal promoter region of NOS2A, the gene encoding inducible nitric oxide synthase. Sequencing 72 Gambian chromosomes revealed 11 single nucleotide polymorphisms in 2.5 kB (theta=8.6 x 10(-4)). Genotyping 104 nuclear families identified six common haplotypes. A single haplotype, uniquely defined by the NOS2A-1659T allele, was associated with cerebral malaria by a transmission disequilibrium test of 334 affected children and their parents (P=0.02). An independent case-control study of 505 different children from the same population replicated the allelic association with cerebral malaria (odds ratio: 1.31, P=0.04). Taken together these data indicate a weak but significant association of the NOS2A locus with susceptibility to cerebral malaria. Despite high linkage disequilibrium across the region studied, this association would not have been detected without the initial construction of a dense marker set for haplotype tagging.